Characterizing World Market Integration through Time - Carrieri, Francesca; Errunza, Vihang; Hogan, Ked (Journal of Financial and Quantitative Analysis, 2007)
Abstract International asset pricing models suggest that barriers to portfolio flows and availability of market substitutes affect the degree and time variation of world market integration. We use GARCH-in-mean methodology to assess the evolution in market integration for eight emerging markets over the period 1977–2000. Our results suggest that while local risk is still a relevant factor in explaining time variation of emerging market returns, none of the countries appear to be completely segmented. We find that there are substantial crossmarket differences in the degree of integration. The evolution toward more integrated financial markets is apparent although at times we do observe reversals. In addition, we provide clear evidence on the impropriety of directly using correlations of market-wide index returns as a measure of market integration. Finally, financial market development and financial liberalization policies play important roles in integrating emerging markets.